The association between gratitude and distress tolerance in undergraduate students: the mediating effect of hope and fear of COVID-19 - Kaya, Esma U.; Kaya, Gamze A. (Taylor & Francis Ltd, 2024)
ObjectiveThe COVID-19 pandemic negatively affected the mental health of people all over the world. The distress tolerance of individuals may make them more resilient to negative emotions. Therefore, this study aimed to examine the mediating roles of hope and fear of COVID-19 in the relationship between gratitude and distress tolerance.MethodThis study was designed as STROBE cross-sectional reporting guidelines, and included 440 health science students enrolled in a public university in Turkey. Participants completed the Gratitude Questionnaire-6, Distress Tolerance Scale, Hope Scale, and Fear of COVID-19 scale.ResultsThe direct link between gratitude and distress tolerance was not significant. Hope was positively associated with gratitude and distress tolerance, whereas fear of COVID-19 was negatively associated with gratitude, hope, and distress tolerance. Hope and fear of COVID-19 do not sequentially mediate the link between gratitude and distress tolerance.ConclusionsThe positive relationship between gratitude and distress tolerance was mediated only by hope. The findings of our study are important as they emphasise that individuals with high dispositional gratitude and hope may improve their distress tolerance abilities. For dispositional gratitude to improve the ability to tolerate distress, additional efforts to provide individuals with this ability may be necessary. What is already known about this topic:(1) The COVID-19 epidemic has increased psychological distress such as anxiety and fear.(2) Poor distress tolerance causes negative emotions to be experienced more intensely.(3) Gratitude and hope improve mental health.What this topic adds:(1) In the COVID-19 epidemic, the relationships between distress tolerance as well as positive (hope and gratitude) and negative psychology (fear of COVID-19) variables were not examined.(2) Gratitude and hope may improve distress tolerance.(3) In order for gratitude to improve distress tolerance ability, skill development training may be needed to equip individuals with this ability.
Keywords: Gratitude; hope; fear of COVID-19; distress tolerance; undergraduate students